Multivariate Analysis Using High Definition Flow Cytometry Reveals Distinct T Cell Repertoires between the Fetal–Maternal Interface and the Peripheral Blood - Neller, Michelle; Santner-Nanan, Brigittie; Brennan, Rebekah; Hsu, Peter; Joung, Steven; Nanan, Ralph; Burrows, Scott; Miles, John J. (Frontiers in Immunology, 2014)
The human T-cell compartment is a complex system and while some information is known on repertoire composition and dynamics in the peripheral blood, little is known on repertoire composition at different anatomical sites. Here, we determine the T-cell receptor β-variable (TRBV) repertoire at the decidua and compare it with the peripheral blood during normal pregnancy and preclampsia. We found total T-cell subset disparity of up to 58% between sites, including large signature TRBV expansions unique to the foetal-maternal interface. Defining the functional nature and specificity of compartment-specific T-cells will be necessary if we are to understand localised immunity, tolerance and pathogenesis.